A new species of the cirripede genus Proverruca Withers, 1914 (Crustacea, Thoracica) from the upper Campanian (Upper Cretaceous) of northeastern Belgium - Gale, Andrew S.; Jagt, John W. M. (Zootaxa, 2025)
A new species of the cirripede genus Proverruca, P. ornata sp. nov., is described from the lower upper Campanian (Belemnitella woodi belemnite Zone) Zeven Wegen Member (Gulpen Formation) at Haccourt, province of Liège, northeastern Belgium. It displays remarkable variation in external sculpture during ontogeny.